Endemicity of acinetobacter calcoaceticus-baumannii complex in an intensive care unit in Malaysia - Dhanoa, A.; Rajasekaran, G.; Lean, S.S.; Cheong, Y.M.; Thong, Kwai Lin (Hindawi Publishing Corporation, 2015)
Introduction. Acinetobacter calcoaceticus-baumannii complex (ACB complex) is a leading opportunistic pathogen in intensive care units (ICUs). Effective control of spread requires understanding of its epidemiological relatedness. This study aims to determine the genetic relatedness and antibiotic susceptibilities of ACB complex in an ICU in Malaysia. Methodology. Pulsed field gel electrophoresis (PFGE), E-test, and disk diffusion were used for isolates characterization. Results. During the study period (December 2011 to June 2012), 1023 patients were admitted to the ICU and 44 ACB complex (blood,